Development and assessment of an improved recombinant multiepitope antigen-based immunoassay to diagnose chronic Chagas disease. Issue 12 (28th March 2018) - Peverengo, Luz María; Garcia, Valeria; Rodeles, Luz María; Mendicino, Diego; Vicco, Miguel; Lagier, Claudia; Gonzalez, Verónica; Gugliotta, Luis; Marcipar, Iván
Abstract: The use of chimeric molecules fusing several antigenic determinants is a promising strategy for the development of low-cost, standardized and reliable kits to determine specific antibodies. In this study, we designed and assessed a novel recombinant chimera that complements the performance of our previously developed chimera, CP1 [FRA and SAPA antigens (Ags)], to diagnose chronic Chagas disease. The new chimeric protein, named CP3, is composed of MAP, TcD and TSSAII/V/VI antigenic determinants. We compared the performance of both chimeric Ags using a panel of 67 Trypanosoma cruzi -reactive sera and 67 non-reactive ones. The sensitivity of CP3 vs CP1 was 100 and 90.2%, and specificity was 92.5 and 100%, respectively. The mixture of CP1 + CP3 achieved 100% of sensitivity and specificity. More importantly, an additional subset of 17 sera from patients with discordant results of conventional serological methods was analysed; the CP1 + CP3 mixture allowed us to accurately classify 14 of them with respect to IIF, the usual technique used in most of the reference centres. These results show an improved performance of the CP1 + CP3 mixture in comparison with enzyme-linked immunosorbent assay and indirect haemagglutination commercial assays.